"A Theoretical Approach to School Success within the Framework of Multicultural Schools " - Mihaela David-Izvernar; Alina Felicia Roman (Babes-Bolyai University, 2023)
A multicultural school is meant to promote inclusive politics and equitable learning opportunities and that in the framework of the winding quest for high educational outcomes for each and every student, regardless of ethnicity and socio-economic backgrounds. School success is not merely the salient knowledge span, it encompasses a set of life skills, parental support, brain power and a myriad of attitudes meant to allow the school leaver not only to avoid depletion, but also to achieve high performance goals and, what's more, to ensure fair treatment to all. Equipped with fortitude, resilience and a team spirit, the school leaver finds thus attainment by taking different educational pathways, from the theoretical to the vocational one. School success is ultimately about finding fulfilment, about leading a quality life and feeling integrated wherever one may be. Taking on challenges in exchanges among the different ethnic groups, making practical use of soft sills to stay connected and agile in such a community, grappling with the link between the school curriculum and the practicalities of the world around, all these might be the tipping point to be analyzed and addressed by the present article. Yet, in a multicultural learning environment attachment to one's cultural values with its spillover implications is far from enough, it must align with keeping all lines of communication open for cultural exchange, even to the point where the exchanges become goals and social and emotional learning go hand in hand with academic achievement.